Phase Change Material of Copper–Germanium Alloy as Solar Latent Heat Storage at High Temperatures - Gokon, Nobuyuki; Jie, Chew Shun; Nakano, Yuya; Okazaki, Shogo; Kodama, Tatsuya; Hatamachi, Tsuyoshi; Bellan, Selvan (Frontiers in Energy Research, 2021)
A copper–germanium alloy (Cu–Ge alloy) was examined as a phase change material, at temperatures exceeding 600 °C, for latent heat storage in solar thermal applications. First, the thermo-physical properties of the Cu–Ge alloy were examined using differential scanning calorimetry, thermomechanical analysis, and laser flash analysis. Second, to evaluate the thermal response and reliability of the Cu–Ge alloy, the cyclic properties of thermal charge/discharge were examined under various thermal conditions. The alloys obtained after the tests were examined for their chemical compatibility with the stainless steel container using an electron probe micro analyzer. The elemental distribution of each Cu–Ge alloy was evaluated using cyclic performance tests. Finally, the chemical compatibility of the Cu–Ge alloy was evaluated using a high-temperature test with candidate materials of a phase change material container vessel (stainless steel (SUS310S), Inconel625, silicon carbide (SiC), and alumina (Al2O3)). The Cu–Ge alloy exhibited significant potential as a latent heat storage material in next-generation solar thermal power plants because it demonstrates various advantages, including a superior storage capacity at a temperature of 644°C, temperature coherence to the phase diagram, a quick thermal response, satisfactory cyclic behavior of charge/discharge modes, a thermodynamically stable metallographic structure, and non-reactivity with container ceramic materials (SiC and Al2O3).